Bioprospecção, isolamento e caracterização parcial de uma lectina presente em sementes da espécie Bauhinia catingae Harms (Fabaceae, Cercidoideae) - Morada, Rebeca Cristian Victor (2024)
Lectins are non-immune proteins that bind to carbohydrates and interact reversibly with specific sugars or glycoconjugates. This group of proteins is widely found in all realms of life and, for decades, has been used as models in the study of the molecular basis of protein-carbohydrate interaction. Despite their wide distribution, plant lectins are the most studied, mainly from the Leguminosae family. Only a few lectins from the Caesalpinioideae subfamily of the legume group have been reported. This highlights the biotechnological potential of these molecules, which is still underexplored. Thus, there are still few existing works on the purification of lectins extracted from the Bauhinia genus, demonstrating the need for more research aiming at an in-depth study of lectins from this genus, as this still understudied group presents lectins with heterogeneous characteristics and interesting and promising biotechnological activities. In this study, a new lectin extracted from Bauhinia catingae Harms seeds (BCL) was isolated using two chromatographic steps on DEAE-Sephacel and Agarose-Lactose columns. BCL has an affinity for galactose and derivatives, like other lectins from the Bauhinia genus, and SDS-PAGE revealed the lectin as a major band around 30 kDa, also similar to other lectins from the genus. BCL showed stability over a small range of temperature and pH and did not appear to be a metalloprotein. The partial sequence of the lectin was partially obtained by electrospray ionization mass spectrometry, and BCL was not toxic to Artemia nauplii. Therefore, it is necessary to continue the structural study of BCL to gain a deeper understanding of this lectin's structure and its possible activities and applications.